El juego recreativo y su incidencia en el desarrollo psicomotriz de los niños de primer grado de educación básica de la escuela Lauro Damerval Ayora N°1 de la ciudad de Loja. Periodo 2013-2014 - Peñarreta Jiménez, Tania Janeth (2014)
This research entitled " THE RECREATIONAL GAME AND ITS IMPACT ON THE DEVELOPMENT OF CHILDREN PSYCHOMOTOR FIRST DEGREE OF BASIC EDUCATION SCHOOL LAURO Damerval AYORA No.1 CITY Loja . PERIOD 2013-2014 "with the overall objective of contributing to improving the quality of learning of children are educated in this school. The methods used for the development of the research were : scientific , analytic-synthetic the same organization , processing, and analysis of information made feasible ; to achieve a survey data was used , the same as was applied to two teachers of the institution; Also a test which was applied to 34 students was developed ; likewise a tab observation was designed to determine motor skills of children through recreational games. Based on the investigation could infer that the momentum of recreational activities helps develop motor skills of infants , keeping them interested and motivated to achieve meaningful learning for the implementation of planned activities.